Evaluation De L’efficacité De Fongicides Au Laboratoire Contre Corynespora Cassiicola, Agent Causal De La Maladie « Corynespora Leaf Fall » De L’hévéa En Côte d’Ivoire - Yao Kouakou Alban Prosper; Wahounou Polié Jean; Diallo Atta Hortense (European Scientific Journal, ESJ, 2018)
Corynespora leaf fall disease (CLFD) caused by Corynespora cassiicola is increasingly a major problem for the development of rubber production in Côte d'Ivoire. In the search for solutions to this problem, the efficacy of 11 fungicides (Azoxystrobin, Carbendazime + Chlorothalonil, Carbendazime, Chlorothalonil, Difenoconazole, Fosetyl-Aluminum, Iprodione, Mancozeb, Metalaxyl + Copper Oxide, Pyraclostrobin + Fenpropimorph, Triadimefon) was laboratory tested against an isolate of C. cassiicola. The results of this test showed a high level of efficacy of four fungicides, Iprodione, Carbendazime + Chlorothalonil, Carbendazim and Pyraclostrobin + Fenpropimorph. The use of these four fungicides formulations in mature plantation would be well indicated, to overcome this foliar pathology.